Intellectual capital and firm's financial distress risk: Evidence from developed and developing countries - Radifan Wisnu Pradana; Dony Abdul Chalid (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study aims to examine the effect of intellectual capital on financial distress risk in developed and developing countries. Design/Methods/Approach: This study adopts a quantitative approach that focuses on investigating the effect of intellectual capital on the risk of financial distress by employing data from 266 companies listed on the India stock Exchange and 1164 companies listed on the Japan Stock Exchange during the period from 2017 to 2021. Panel data regression is employed to conduct the statistical analysis. Findings: The results confirm that firms in developing and developed socioeconomic backgrounds with stronger intellectual capital are less likely to face financial distress. While the overall impact of intellectual capital on the risk of financial distress appears consistent, the magnitude of each category of intellectual capital varies depending on the economic circumstant. The influence of human capital efficiency in reducing financial distress risk is observed to be stronger in developed countries when comparing the value of the regression coefficient. In contrast, capital-employed efficiency has a greater impact on lowering financial distress risk in emerging nations. Originality: This study uses the Adjusted VAIC (Value-Added Intellectual Coefficient) method, which incorporates research and development data in measuring structural capital, addressing criticisms faced by the original VAIC method. This study also explores the association between intellectual capital and the risk of financial distress, offering insights into the predictive value of intellectual capital indicators for identifying financially distressed companies. This research examines two countries with differing socioeconomic development and emphasizes intellectual capital's role in developing and developed economies. Additionally, utilizing the Z-Score measurement, adapted for emerging markets in the case of India, provides a comprehensive assessment of the financial distress risk. Practical/Policy implication: Based on the results, managers should prioritize financial investments that impact the organization's resources, considering the influence of capital employed on intellectual capital. Although less influential, human capital remains significant, thereby emphasizing the importance of investing in employee development and fostering collaboration. While innovation capital may not exhibit statistical significance, creating an environment that supports innovation still holds considerable value.